Cohesion and Genre Blending in Prophetic Literature, Using Amos 5 as a Case Study - Toffelmire, Colin M. (2021)
This study draws on Systemic Functional Linguistics and Cognitive Theory to explore genre blending in Amos 5. It demonstrates that Amos 5 is both a plausibly cohesive and coherent text, and that the text is made up of sub-sections of identifiably distinct genres of prophetic literature.